The Situation of Speech Diglossia in Madurese Gili Ketapang Village Community, Sumberasih District, Probolinggo Regency - Magfirotul Hamdiah; Rohmah, Nur; Amelia Widya Hanindita (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2023)
This study aims to describe the situation of diglossia in the community in Gili Ketapang village, Suberasih District, Probolinggo Regency. The research design uses a qualitative approach with qualitative descriptive methods. The results of the study generally show that the situation of diglossia in the family realm is influenced by the personality of the speaker. One can use the subtle Madurese language because of two possibilities, namely the social level of the family and the background of the Islamic boarding school. The situation is diglossia in the realm of religion, the people of Gili Ketapang Village are more dominant in using fine variations of the Madurese language and also rough variations to make it easier to understand the meaning conveyed by speakers. In the situation of diglossia in the social sphere, especially in the community of Gili Ketapang Village, it is more dominant to use the Madurese language in subtle variations in various events. In the realm of education and work/profession, the situation of diglossia of language selection used by speakers is smooth Madurese as a polite variety of Madurese and there is also intermingling with Indonesian as the national language.